Circular Resolution, Conflict of Interest, and Corporate Bankruptcy: A Legal Study of the Actions of Directors as Shareholders - Zulfikar Ardiwardana Wanda; Muhammad Dito Zakharia (Unram Law Review, 2026)
A Limited Liability Company (PT) as a legal entity, has a decision-making mechanism that, in principle, is implemented through a General Meeting of Shareholders (RUPS). However, Law No. 40 of 2007 on Limited Liability Companies also recognizes a decision-making mechanism outside the RUPS through bulletin decisions as a more efficient alternative. Legal issues arise when bulletin decisions are used in strategic agendas such as voluntary bankruptcy petitions, especially in situations where Directors also act as shareholders. This situation has the potential to create conflicts of interest, especially if the bankruptcy of the corporation is due to the mistakes or neglect of the relevant Directors. This is a normative legal study with a legislative and conceptual approach, which aims to analyze bulletin decisions and the implications of the bulletin decision mechanism on the responsibility of the Director's Board in bankruptcy cases. The study finds that circular resolutions can be misused to avoid responsibilities regulated in Article 104 of Law Number 40 of 2007 concerning Limited Liability Companies, given that circular resolutions require unanimous shareholder approval. This study emphasizes the importance of reforming the circular resolution mechanism.